Computational Modelling of a Sensor Based on an Array of Enzyme Microreactors - Baronas, R.; Ivanauskas, F.; Kulys, J.; Sapagovas, M. (Nonlinear Analysis: Modelling and Control, 2004)
This paper presents a two-dimensional-in-space mathematical model of a sensor system based an array of enzyme microreactors immobilised on a single electrode. The system acts under amperometric conditions. The model is based on the diffusion equations containing a non-linear term related to the Michaelis-Menten kinetics of the enzymatic reaction. The model involves three regions: an array of enzyme microreactors (cells) where enzyme reaction as well as mass transport by diffusion takes place, a diffusion limiting region where only the diffusion takes place, and a convective region, where the analyte concentration is maintained constant. Using computer simulation the influence of the geometry of the enzyme cells and the diffusion region on the biosensor response was investigated. The digital simulation was carried out using the finite difference technique.
Keywords: reaction-diffusion; modelling; biosensor; microreactor